Mineralocorticoid receptor stimulation induces urinary storage dysfunction via upregulation of epithelial sodium channel expression in the rat urinary bladder epithelium - Seiji Yamamoto; Yuji Hotta; Kotomi Maeda; Tomoya Kataoka; Yasuhiro Maeda; Takashi Hamakawa; Shoichi Sasaki; Takahiro Yasui; Kiyofumi Asai; Kazunori Kimura (Elsevier, 2016)
We aimed to evaluate mineralocorticoid receptor (MR) expression in rat bladder and the physiological role of the MR-epithelial sodium channel (ENaC) pathway in controlling bladder function in 10-12-week-old, male Sprague-Dawley rats. First, we examined the mRNA expression of MR and localization of MR and ENaC-α proteins in the urinary bladder. MR mRNA expression was observed in untreated-rat urinary bladders, and MR and ENaC-α proteins were localized in the epithelium. Next, rats were treated with vehicle (controls) or fludrocortisone (an MR agonist) for 3 days, and ENaC-α protein expression levels and bladder function were evaluated on day 4. ENaC-α protein expression was significantly higher in fludrocortisone-treated rats than in controls. In addition, cystometry was performed during intravesical infusion of saline and amiloride (an ENaC inhibitor). While intercontraction intervals (ICIs) during saline infusion were significantly shorter in the fludrocortisone group than in the controls, infusion of amiloride normalized the ICIs in the fludrocortisone group. However, no intra- or inter-group differences in maximum intravesical pressure were observed. Taken together, MR protein is localized in the rat urinary bladder epithelium, and may regulate ENaC expression and bladder afferent input. The MR-ENaC pathway may be a therapeutic target for ameliorating storage symptoms.